Testing a Prototype of Interactive Semantic Analyzer (PISA) - Choul, Jean-Claude (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1990)
This paper uses Borland’s Turbo Prolog version 2.0 as a formalizing tool to test the basic assumptions of a Value Assignment Semantic Theory. A Prolog rule is conditional, just as a meaning assignment is a value attributed IF certain conditions are satisfied. Semantic analysis thus becomes the study of conditions governing a sense attribution. As a Prolog clause, meaning is a relation holding between two arguments of a sense predicate where metalinguisic equivalence is the most economical way of describing meaning.